EXISTING PROBLEMS ANALYZIS OF ORGANIZATIONAL AND TECHNOLOGICAL RELIABILITY OF ROOFING SYSTEMS - Radkevich, A. V.; Khudenko, V. F.; Glushenko, V. M. (Science and Transport Progress, 2015)
Purpose. The article aims at analysis of existing approaches towards engineering, construction, reconstruction and major repair of buildings roofing systems and constructions for solving the matters regarding organizational and technological reliability. Methodology. The survey is based on methods of analogy, scientific analysis and synthesis. Findings. The analysis of innovative technologies as well as new construction materials for roofing has been carried out. Problems regarding their organizational and technological reliability have been specified. Relevance of the given problems has been grounded. Correlation between reliability of constructed facility or roofing repair from thoroughly chosen technology and also construction process organization in general was determined. All the specifications influencing roofing organizational and technological reliability have been divided into primary and secondary. New methodic conception including all the constituents of roofing in the whole has been worked out. Ukrainian and European specification documents have been taking into account. Roofing organizational and technological reliability scheme considering the factors that form reliability has been suggested. An urgent need for creation of roofing model taking into consideration the innovative technologies and latest roofing materials for choosing its rational variant has been emerged. It has to meet both customers and specification documents requirements and also desired level of organizational and technological reliability. Originality. For the first time the notion of «organizational and technological reliability» has been applied to roofing. Fundamental investigation of this notion has been suggested. Roofing reliability dependence on all its components as a whole has been analyzed. New approach towards roofing problems solving conception has been developed. Practical value. The survey results may be applied at roofing engineering and construction organizations activity analysis. Investigation results have practical value in roofing with desired reliability engineering.